CYP2C19*17 Gain‐of‐Function Polymorphism Is Associated With Peptic Ulcer Disease. Issue 2 (26th October 2012) - Musumba, C O; Jorgensen, A; Sutton, L; Van Eker, D; Zhang, E; O'Hara, N; Carr, D F; Pritchard, D M; Pirmohamed, M
<x xml:space="preserve">Abstract</x> Single‐nucleotide polymorphisms (SNPs) in the CYP2C gene cluster have been extensively investigated as predisposing factors for nonsteroidal anti‐inflammatory drug (NSAID)‐induced peptic ulcer disease (PUD) or upper gastrointestinal bleeding (UGIB). However, results have been inconclusive owing to different study designs, limited genotyping strategies, and small sample sizes. We investigated whether eight functional SNPs in the CYP2C family of genes—CYP2C8*3 (rs11572080 and rs10509681), CYP2C8*4, CYP2C9*2, CYP2C9*3, CYP2C19*2, CYP2C19*3, and CYP2C19*17—are associated with PUD in 1, 239 Caucasian patients. Logistic regression analysis showed that only CYP2C19*17 was associated with PUD (odds ratio additive model: 1.47 (95% confidence interval (CI) 1.12 to 1.92); P = 0.005; R2 16%), but not UGIB, independent of NSAID use or Helicobacter pylori infection. PUD distribution varied (P = 0.024) according to CYP2C19*17 genotype: *1/*1, 490 (64.3%); *1/*17, 304 (71.7%); and *17/*17, 31 (73.8%). CYP2C19*17, a gain‐of‐function polymorphism, is associated with PUD irrespective of etiology. Clinical Pharmacology & Therapeutics (2013); 93 2, 195–203. doi:10.1038/clpt.2012.215